Size Dependent Uniaxially Loaded Stability of Triaxial Weave Fabric Composites - Muhammad Nor, Hafidzi; Ahmad Kueh, Beng Hong; Norhidayah, Rasin; Airil Yasreen, Mohd Yassin; Hisham, Mohamad (Trans Tech Publications, Switzerland, 2011)
This paper explores the size effects on the stability of simply supported triaxial weave fabric (TWF) composites subjected to a uniaxial compressive load. Three material expressions: homogenized, segmentation, and classical lamination theory are subscribed as the constitutive relation for the 2D composite finite element model used in the study. Remarkable dependency of critical buckling load on the material size is exhibited in all models, the least affected being those of homogenized and segmentation.